2020
DOI: 10.1038/s41467-020-15072-8
|View full text |Cite
|
Sign up to set email alerts
|

Acid ceramidase of macrophages traps herpes simplex virus in multivesicular bodies and protects from severe disease

Abstract: Macrophages have important protective functions during infection with herpes simplex virus type 1 (HSV-1). However, molecular mechanisms that restrict viral propagation and protect from severe disease are unclear. Here we show that macrophages take up HSV-1 via endocytosis and transport the virions into multivesicular bodies (MVBs). In MVBs, acid ceramidase (aCDase) converts ceramide into sphingosine and increases the formation of sphingosine-rich intraluminal vesicles (ILVs). Once HSV-1 particles reach MVBs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 74 publications
0
33
0
Order By: Relevance
“…In this study we observed that beside ω-N 3 -C 6 -ceramide 16 an azido-modified sphingosine, ω-N 3 -sphingosine 22 , exhibited significant bactericidal activity. We show that an observable effect on bacteria of both modified sphingolipid analogs is distortion of the cell membrane.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In this study we observed that beside ω-N 3 -C 6 -ceramide 16 an azido-modified sphingosine, ω-N 3 -sphingosine 22 , exhibited significant bactericidal activity. We show that an observable effect on bacteria of both modified sphingolipid analogs is distortion of the cell membrane.…”
Section: Discussionmentioning
confidence: 79%
“…The data demonstrated a potent bactericidal activity of sphingosine and the synthetic ceramide analog ω-N 3 -C 6 -ceramide against N. meningitidis 13 . Here, we now determined the MIC and MBC values for a newly synthesized sphingosine analog, ω-N 3 -sphingosine 22 , against N. meningitidis . ω-N 3 -sphingosine displayed a MIC value of 4 µg/ml and a MBC value of 8 µg/ml comparable to MIC/MBC values observed for the unmodified sphingosine for N. meningitidis (Table S1 ) 13 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the overall inhibition of ceramidase activity in host peripheral blood lymphocytes using Ceranib 1 and Ceranib 2 significantly reduces the replication of the rhinovirus and measles virus, respectively [ 110 , 111 ]. Furthermore, the inhibition of ACDase activity in macrophages significantly increases the propagation of herpes simplex virus-1, which, in turn, elevates the mortality rate in Asah1 −/− mice [ 112 ].…”
Section: Role Of Ceramidase Activity In Infectious Diseasesmentioning
confidence: 99%